Synthesis, characterization and antibacterial activity study of platinum(II) complex with quinoline ligand - Dr. Rajaa A. Hussein (Al-Qadisiyah Journal of Pure Science, 2017)
Cis-dichloro(quinoline)2Platinum(II)complex [(Qu.)2PtCl2] was prepared using quinoline as non-leaving ligand and chloride ion Cl- as leaving group.Platinum(II) complexes was characterized based on infrared spectral and UV-visible measurements, and screened in vitro for their biological activity (both antimicrobial and cytotoxicity). All results were compared with cisplatin and standard free ligand. The compound to be tested was dissolved in dimethylsulfoxide DMSO, thus solvent was used as negative control and cisplatin was analyzed as the positive control.Antimicrobial activity against gram negative bacteria Escherichia coli and gram positive Staphylococcus aureus, show that Cis- [(Qu.)2PtCl2] complex exhibit strong antibacterial activity (27.5, 25, mm respectively) against both tested bacteria as compared with free ligand and cisplatin.Finally, the effect of prepared complex on human red blood cells hemolysis was investigated, found that [(Qu.)2PtCl2] complex caused simple cells hemolysis in vitro about 2.597%) as compared with cisplatin (5.050 %) .In the present investigation, all results obtained indicate that quinoline ligand plays an important role in the synthesis of new platinum complexes with high efficacy and low toxicity compared with cisplatin anticancer drug.